Strategi Manajemen Keuangan yang Efektif untuk Mengurangi Stres Kerja di Lingkungan Kerja Lurah Harjosari II - Aswin Akbar; NAZMAH; Dian Purnama Sari (Jurnal Masyarakat Indonesia (Jumas), 2024)
Work stress is an increasingly concerning issue in the modern work environment, including at Lurah Sitiharjo II. Excessive work stress can negatively impact employees' physical and mental health, reduce productivity, and lower job satisfaction. Work stress occurs when there is an imbalance between job demands and an individual's ability to meet those demands. At Lurah Sitiharjo II, administrative pressure, high public service demands, and limited resources often become major sources of stress for employees. Effective financial management is often overlooked as a means to reduce work stress. Good financial management provides stability and peace of mind, which helps alleviate stress. Research shows that poor financial management is a significant factor in causing work stress. Financial literacy and well-being programs can significantly reduce work stress levels by enhancing employees' understanding and skills in managing personal finances. Industrial and organizational psychology approaches indicate that effective financial management can increase motivation and job satisfaction. Employees who feel financially secure are more likely to show high commitment to the organization and have good relationships with colleagues and supervisors. Therefore, integrating effective financial management strategies into Lurah Sitiharjo II's policies not only improves employees' financial well-being but also reduces work stress, enhances job satisfaction, and boosts organizational productivity. This study aims to examine the relationship between effective financial management and the reduction of work stress at Lurah Sitiharjo II, as well as to identify best practices that can be implemented.